Performance of different herbicides in a dry-seeded rice system in Sri Lanka - Chauhan, Bhagirath S.; Abeysekara, Anuruddika S.K.; Kulatunga, Sakinda D.; Wickrama, Upali B. (Cambridge University Press, 2013)
Dry-seeded rice systems are an emerging production technology in many Asian countries. A field study was conducted in 2011 and 2012 at the farm of the Rice Research and Development Institute, Batalagoda, Sri Lanka, to evaluate the performance of different herbicides in a dry-seeded rice system. Weed control treatments were nontreated (weedy), pretilachlor plus pyribenzoxim, cyhalofop-butyl, thiobencarb plus propanil, propanil, and bispyribac-sodium plus metamifop. All these POST herbicides were applied at 8 d after sowing, followed by an MCPA spray at 20 d after sowing. The dominant weeds in the study were barnyardgrass, Chinese sprangletop, and knotgrass. All herbicide treatments provided similar weed control, which ranged from 82 to 99%. Weeds in the nontreated plots reduced rice grain yield by 58 to 79% compared with the herbicide-treated plots. All herbicide-treated plots, except cyhalofop-butyl-treated ones, produced similar grain yield, which ranged from 3.7 to 4.2 t ha−1 in 2011 and from 6.0 to 7.0 t ha−1 in 2012. The results of our study suggest that different herbicides provided similar weed control and therefore different herbicides can be rotated in different seasons to reduce selection pressure on weeds.